التفكير اللساني المعاصر، والقراءة النقدية التأويلية - بعداش، ناصر (جامعة عمار ثليجي بالأغواط - كلية الآداب, 2019)
إن النظرة الحديثة في مجال الدراسات النقدية خطت خطوات هامة في تناول النصوص بالدراسة ومعالجتها، وبالتالي فقد ركزت مرحلة البنيويات والسيميائيات وغيرها من المناهج على النص بشكل من الأشكال، مقصية بذلك المؤلف والمرجع والسياق والإحالة، ولما كان ذلك كذلك فقد تم التركيز على النص تركيزاً كليا؛ باعتباره مجموعة من البنيات الداخلية المغلقة ذات الدلالات الكثيرة، ومجموعة من العلامات اللغوية والأيقونات البصرية، وكان هذا الاهتمام على حساب القارئ الذي اهتمت به هذه الدراسات، وركز عليه العديد من الباحثين، نظراً للدور الكبير الذي يلعبه في عملية القراءة والتأويل والإدراك والسرد والقص، وكان ذلك بعد عناية علماء النفس والمؤرخين وكتاب السير بالمؤلف، وإهمالهم الواضح للنص على الرغم من أنه هو الأساس، ومنه: -إلى أي مدى يمكن اعتبار النص هو الأساس في عملية القراءة والتأويل؟ -هل التفكير اللساني المعاصر نجح في تخطي دور المؤلف؛ والانتقال إلى دور القارئ؟ -ما الدافع إلى التأويل، أهو الغموض الذي يطغى على النصوص؟ أم ذلك التعقيد اللفظي والمعنوي الذي يتقصده المرسل؟ وإذا كان موضوع النقد الأدبي هو العمل الأدبي فما هو موضوع نظريات تلقي العمل الأدبي؟ أهو كفاءات القارئ؟ أهو النص الذي تظهر من خلاله هذه الكفاءات؟ أهو علاقة التأثير والتأثر بين النص وقارئه؟
The modern outlook in the area of critical studies has taken important steps in the study of the texts, thus, the stage of structuralism semiemies and other approaches focused on the text in some form, thus eliminating the author reference. Context and reference, a group of internal structures closed with many signee, and a set of linguistic signs and visual icons, and this interest at the expense of the reader, with was interested in these studies, and focused by many researchers because of the great role played in the process of reading and interpretation has emerged the latter is in these different and varied as an effective element in the handling of the text and the process of analysis interpretation, cognition, narration, and storytelling, this was after the attention of psychologists, historians, and book writers, and their obvious neglect of the text although it is basis: -To what extent can the text be considered the basis of reading and interpretation? -Has modern linguistic thinking succeeded in overcoming the role of the author, and moving to the role of reader? - What is the reason for interpretation is the ambiguity that prevails over text? Or the verbal and moral complexity of the sender? - If the subject of literary criticism is literary work? What is the subject of the theories of receiving literary work? What is the competency of the reader? Is it the text that shows these competencies? what is the relation between the text and the reader?
Keywords: اللسانيات المعاصرة -- النقد الأدبي -- القراءات التأويلية -- النصوص الإبداعية